Design of technology-enhanced learning : integrating research and practice - Bower, Matt (Emerald Publishing, 2017)
This book explains how educational research can inform the design of technology-enhanced learning environments. After laying pedagogical, technological and content foundations, it analyses learning in Web 2.0, Social Networking, Mobile Learning and Virtual Worlds to derive nuanced principles for technology-enhanced learning design.
Keywords: Educational technology.; Education -- Effect of technological innovations on.; Web-based instruction.; elektronické knihy; electronic books